The Influence of Leadership and Competence on Work Motivation and its impact on Employee Performance at the Koto Besar Sub-District Office, Dharmasraya Regency - Yusrisal, Yusrisal; Heryanto, Heryanto (Archives of Business Research, 2019)
This study tries to test the Effect of Leadership, Competence and Work Motivation on Employee Performance in Koto Besar District, Dharmasraya Regency. This study uses descriptive quantitative methods. The study population consisted of 52 people from employees. To obtain a valid and realistic instrument, the validity and reliability test, normality test, multicollinearity test and heterocedasticity test were tested. The data analysis technique used is path analysis. The results showed that leadership and competency styles had a significant influence on the performance of employees of the Koto Besar Sub-District office in Dharmasraya Regency. Leadership and Competence styles did not have a significant influence on the motivation of employees of the Koto Besar Sub-District Head Office in Dharmasraya District, motivation did not have much influence between leadership and performance. The empirical findings indicate that in order to improve Community Satisfaction, the Koto Besar Sub-District Office of Dharmasraya District needs to pay attention to the performance of the staff of the Koto Besar Sub-District Office in Dharmasraya Regency.